STUDI LITERATUR: STRATEGI MANAJEMEN KONFLIK UNTUK MENINGKATKAN TEAMWORK DALAM ORGANISASI - Albarika Kharisma Safira; Aulia Kamalia; Rafina Safri Dewi; Siti Hujrotun Shopiah; Tia Silvia (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze conflict management strategies that can be effectively applied to enhance teamwork within organizations. Conflict often arises as a consequence of differences in perspectives, values, interests, or roles among team members. Rather than being viewed solely as a disruptive element, conflict can serve as a constructive force when managed properly. This research adopts a qualitative approach through a literature review method. Data were collected from a variety of academic sources including scholarly journals, books, and prior research studies relevant to the topics of conflict and teamwork. The findings reveal that conflict management strategies such as collaboration, compromise, internal mediation, communication training, and the establishment of team norms are proven effective in strengthening teamwork. These strategies not only resolve interpersonal tensions but also reinforce the social fabric of the team, contributing to a more positive and productive work environment. The success of such implementations is largely influenced by open leadership, an organizational culture that supports dialogue, and the team’s readiness to cooperate and adapt. This study recommends that organizations embed conflict management practices as an integral part of their team development programs. With the right approach, conflict can become an opportunity to strengthen cooperation and achieve organizational goals more effectively.